An international multicenter cohort study on implantable cardioverter-defibrillators for the treatment of symptomatic children with catecholaminergic polymorphic ventricular tachycardia - Lamba, Avani; Roston, Thomas M.; Peltenburg, Puck J.; Kallas, Dania; Franciosi, Sonia; Lieve, Krystien V. V.; Kannankeril, Prince J.; Horie, Minoru; Ohno, Seiko; Brugada, Ramon; Aiba, Takeshi; Fischbach, Peter; et al. (Heart rhythm, 2024)
Background - Catecholaminergic polymorphic ventricular tachycardia (CPVT) may cause sudden cardiac death (SCD) despite medical therapy. Therefore, implantable cardioverter-defibrillators (ICDs) are commonly advised. However, there is limited data on the outcomes of ICD use in children. - Objective - The purpose of this study was to compare the risk of arrhythmic events in pediatric patients with CPVT with and without an ICD. - Methods - We compared the risk of SCD in patients with RYR2 (ryanodine receptor 2) variants and phenotype-positive symptomatic CPVT patients with and without an ICD who were younger than 19 years and had no history of sudden cardiac arrest at phenotype diagnosis. The primary outcome was SCD; secondary outcomes were composite end points of SCD, sudden cardiac arrest, or appropriate ICD shocks with or without arrhythmic syncope. - Results - The study included 235 patients, 73 with an ICD (31.1%) and 162 without an ICD (68.9%). Over a median follow-up of 8.0 years (interquartile range 4.3-13.4 years), SCD occurred in 7 patients (3.0%), of whom 4 (57.1%) were noncompliant with medications and none had an ICD. Patients with ICD had a higher risk of both secondary composite outcomes (without syncope: hazard ratio 5.85; 95% confidence interval 3.40-10.09; P < .0001; with syncope: hazard ratio 2.55; 95% confidence interval 1.50-4.34; P = .0005). Thirty-one patients with ICD (42.5%) experienced appropriate shocks, 18 (24.7%) inappropriate shocks, and 21 (28.8%) device-related complications. - Conclusion - SCD events occurred only in patients without an ICD and mostly in those not on optimal medical therapy. Patients with an ICD had a high risk of appropriate and inappropriate shocks, which may be reduced with appropriate device programming. Severe ICD complications were common, and risks vs benefits of ICDs need to be considered.
Online verfügbar: 7. April 2024, Artikelversion: 30. September 2024
Gesehen am 14.05.2025